Pengaruh Green Marketing dan Kesadaran Lingkungan terhadap Keputusan Pembelian (Survei pada Konsumen Point Coffee) - Afandi, Muh. Imam; Rusmala, Eka; Astriyanti, Venny; Maisara, Dini; Fitri, Fitri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Indonesia suffered environmental damage as a result of a lack of public awareness.  The situation is worsened by the rise in garbage and industry in the agribusiness sector.  In the age of technology, people are beginning to be aware of environmental sustainability, encouraging entrepreneurs to switch to green marketing.  The study aims to analyze the influence of green marketing and environmental awareness on the decision to buy coffee at the point of coffee by the Z generation in Western Sulawesi.  This study uses descriptive quantitative methods with cross sectional research design. Data collected through a survey of 94 Z generation respondents in the district of Majene and Polewali Mandar. Data analyzed using the Partial Least Square Structural Equation Model. (PLS-SEM).  Research shows that green marketing and environmental awareness have a positive influence on the point-of-coffee purchasing decisions of the Z generation.